Bladder afferent hyperexcitability in bladder pain syndrome/interstitial cystitis. (April 2014) - Yoshimura, Naoki; Oguchi, Tomohiko; Yokoyama, Hitoshi; Funahashi, Yasuhito; Yoshikawa, Satoru; Sugino, Yoshio; Kawamorita, Naoki; Kashyap, Mahendra P; Chancellor, Michael B; Tyagi, Pradeep; Ogawa, Teruyuki
Abstract: Bladder pain syndrome/interstitial cystitis is a disease with lower urinary tract symptoms, such as bladder pain and urinary frequency, which results in seriously impaired quality of life of patients. The extreme pain and urinary frequency are often difficult to treat. Although the etiology of bladder pain syndrome/interstitial cystitis is still not known, there is increasing evidence showing that afferent hyperexcitability as a result of neurogenic bladder inflammation and urothelial dysfunction is important to the pathophysiological basis of symptom development. Further investigation of the pathophysiology will lead to the effective treatment of patients with bladder pain syndrome/interstitial cystitis.